Teachers' noticing of the social development of students with special needs - Di Placido, Cinzia (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
Learning disabilities are common among students in grades K-12. When I was a student teacher, I noticed that students with learning disabilities were struggling socially both in and outside of the classroom. As such, I decided to explore this aspect, but through a teacher’s point of view where I interviewed four individuals who are professionals in the field of education. Findings suggest that teachers felt that the social competence of students with learning disabilities is dependent on whether they acknowledge their learning disability. Moreover, teachers believed they (as teachers) played a role in helping students with learning disabilities to overcome their social challenges; however, teachers did not feel prepared to help students overcome such challenges.